Evolution of Rehabilitation Counseling in Puerto Rico: Organizational and Legislative Efforts - Villafañe Santiago, Ángel A. (2013)
The purpose of this paper is to explain a) the historical, organizational, and legislative efforts that have contributed to the development of the Rehabilitation Counseling profession, b) how these efforts have contributed to the development of the professional identity of the rehabilitation counselors and c) how these events have contributed to the development of programs and the provision of quality services to people with special needs in Puerto Rico. Through oral history and literature review, it is possible to recognize the importance of the establishment of the federal legislation that promoted the first program of services to people with special needs in the United States and Puerto Rico. Those legislative mandates have also promoted the development of the Rehabilitation Counseling profession in the 20th Century and the development of professional organizations that have been determinant for the professionalization. This paper illustrates how at the end of 1960, in Puerto Rico, the creation of the Rehabilitation Counselors Association (Asociación de Consejeros en Rehabilitación, ACER by its Spanish acronym) was critical for the transformation of the profession and for the creation of the Puerto Rico’s Professional Society of Rehabilitation Counselors (Colegio Profesional de los Consejeros en Rehabilitación de Puerto Rico) at the beginning of the 21st Century. The study refers to the subsequent legislative efforts and the approval of new mandates as the amendment to the Puerto Rican Law of Mental Health made to include the Rehabilitation Counseling professionals among the professionals authorized to provide such services to people with mental health conditions in the country. After this theoretical historical review, it is concluded that although more marketing is required in terms of promoting the profession, this innovative profession has kept up-to-date over time, and that is a guarantee of the professional commitment to continue providing quality services to the persons with special needs.